Broadband convolutional scattering characteristics of all dielectric transmission Pancharatnam–Berry geometric phase metasurfaces - Li, Yiyun; Jin, Yongxing; Jing, Xufeng; Shi, Lijiang; Li, Chenxia; Hong, Zhi (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
In order to obtain the broadband scattering characteristics, we propose a superperiodic cell structure with all-dielectric material to construct Pancharatnam–Berry geometric phase encoding metasurfaces. Because we cannot design or prepare infinitesimal coding unit particles, according to the generalized Snell’s law, we can only obtain discrete scattering angle regulation for the basic coding metasurface sequence. In order to obtain multi-angle scattering characteristics, we introduce the Fourier convolution principle in digital signal processing on the Pancharatnam–Berry geometric phase encoding metasurfaces. By using the addition and subtraction operations on two encoding metasurface sequences, a new encoding metasurface sequence can be obtained with different deflection angle. Fourier convolution operations on the encoding metasurfaces can provide an efficient method in optimizing encoding patterns to achieve continuous scattering beams. The addition and subtraction methods are also applicable to the checkerboard coding mode. The combination of Fourier convolution principle and Pancharatnam–Berry phase coded metasurface in digital signal processing can realize more powerful electromagnetic wave manipulation capability.
Optica Applicata, Vol. 52, 2022, nr 2, s. 297-323
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; grating; metasurface; optics devices